ULTRASTRUCTURAL CHANGES IN PULMONARY HEMOMICROCIRCULATION AT ACUTE EXPERIMENTAL PANCREATITIS - Zaiats, L.M.; Cherkasova, V.V. (World of Medicine and Biology, 2018)
Experiment performed on 70 white male rats of the Vistar line by electron microscopic method, dynamics (12, 24, 48, 72 h) of ultrastructural changes of the hemomycocirculatory bed of lungs in experimental acute pancreatitis was studied. Established, that at 12 h after the beginning of the experiment there are violations of the submicroscopic structure of the hemomycocirculatory bed of the lungs. In hemocapillaries of the alveolar wall, excessive accumulation of leukocytes, their adhesion and aggregation is noted. With the duration of the study (24-72 h) in the hemomicrocirculatory bed of the lungs are defined as dystrophic-destructive as compensatory-adaptive changes.
Keywords: lungs; hemomicocirculatory bed; acute experimental pancreatitis